2021
DOI: 10.1097/wco.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in secondary prevention of ischemic stroke: how may blood-based biomarkers help in clinical routine? An expert opinion

Abstract: Purpose of reviewOne in eight patients unfortunately suffers a new stroke within 5 years of their first stroke, even today. Research in precision medicine could lead to a more individualized treatment allocation, possibly achieving lower recurrence rates of ischemic stroke. In this narrative review, we aim to discuss potential clinical implementation of several promising candidate blood biomarkers. Recent findingsWe discuss specifically some promising blood-based biomarkers, which may improve the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…A plethora of literature exists on single biomarkers and their ability to predict mortality, or functional disability. 24 The interest increasingly shifts from studying one biomarker to studying biomarker panels which accumulate the information of various biomarkers into one score representing the heterogeneity of a disease. One recent study with 3405 patients showed a higher risk for death at 3 months after stroke if five combined biomarkers were elevated (high-sensitivity C-reactive protein, matrix metalloproteinase-9 (MMP-9), complement C3, antiphosphatidylserine antibodies, hepatocyte growth factor) adjusted for clinical covariates (OR 5.67, 95% CI: 1.09–29.52).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A plethora of literature exists on single biomarkers and their ability to predict mortality, or functional disability. 24 The interest increasingly shifts from studying one biomarker to studying biomarker panels which accumulate the information of various biomarkers into one score representing the heterogeneity of a disease. One recent study with 3405 patients showed a higher risk for death at 3 months after stroke if five combined biomarkers were elevated (high-sensitivity C-reactive protein, matrix metalloproteinase-9 (MMP-9), complement C3, antiphosphatidylserine antibodies, hepatocyte growth factor) adjusted for clinical covariates (OR 5.67, 95% CI: 1.09–29.52).…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of literature exists on single biomarkers and their ability to predict mortality, or functional disability. [2][3][4] The interest increasingly shifts from studying one OR for the BPI corresponds to an increase per unit of the index. biomarker to studying biomarker panels which accumulate the information of various biomarkers into one score representing the heterogeneity of a disease.…”
Section: //mentioning
confidence: 99%
See 2 more Smart Citations
“…45 Unfortunately, one in eight patients can have another stroke within 5 years of their first stroke due to the negligence in prevention, and recurrent strokes are often more severe than the first. 66 Therefore, prevention of stroke is more important than the treatment. The Mediterranean diet is one of the most respected diets for excellent stroke prevention effects due to the richness in fiber, flavonoids and antioxidants.…”
Section: Mechanism Of Apg In the Prevention Of Cerebral Ischemiamentioning
confidence: 99%